2020
DOI: 10.1371/journal.pone.0232294
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous diethyl aminoethyl hexanoate ameliorates low temperature stress by improving nitrogen metabolism in maize seedlings

Abstract: Spring maize sowing occurs during a period of low temperature (LT) in Northeast China, and the LT suppresses nitrogen (N) metabolism and photosynthesis, further reducing dry matter accumulation. Diethyl aminoethyl hexanoate (DA-6) improves N metabolism; hence, we studied the effects of DA-6 on maize seedlings under LT conditions. The shoot and root fresh weight and dry weight decreased by 17.70%~20.82% in the LT treatment, and decreased by 5.81%~13.57% in the LT + DA-6 treatment on the 7 th day, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…This is consistent with the results obtained by Zhang et al. (2020) in a low‐temperature experiment on corn. This indicates that the damage to wheat florets by low temperatures may be related to an imbalance in endogenous nitrogen metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the results obtained by Zhang et al. (2020) in a low‐temperature experiment on corn. This indicates that the damage to wheat florets by low temperatures may be related to an imbalance in endogenous nitrogen metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…This liberated H 2 O 2 is further detoxified by the catalytic action of POD, CAT, or ASA-GSH cycle ( Fotopoulos et al, 2010 ; Hasanuzzaman et al, 2019 ). Previous studies have reported that DA-6 application improved antioxidant activities to alleviate oxidative damage in strawberry ( Fragaria × ananassa ) seedlings under cold stress ( Fu et al, 2011 ), in Cassia obtusifolia under salt stress ( Zhang et al, 2016 ), and in maize under low temperature stress ( Zhang et al, 2020 ). We observed that seeds exposed to water deficient condition significantly increased O 2 – and H 2 O 2 content, however, DA-6 priming greatly alleviated the drought-induced increases in O 2 – and H 2 O 2 accumulation ( Figure 6 ) associated with increases in the activities of antioxidant enzymes (SOD, POD, CAT, or APX) and the expression levels of genes encoding antioxidant enzymes ( FeSOD, MnSOD, Cu/ZnSOD, POD , or CAT ) during seed germination under water stress ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of root bleeding sap contains organic matter synthesized by roots, which is transported from the roots to the aboveground parts [35]. Maize roots mainly absorb NO 3 − , part of which is reduced to NH 4 + by nitrate reductase and nitrite reductase [36]. Moreover, some of NH 4 + is transported upward through the xylem, while the remainder is assimilated into organic nitrogen [37].…”
Section: Discussionmentioning
confidence: 99%